Analysis determinants of social media acceptance in higher educational institution of Pakistan - Raza, Ali; Chandio, Shah Murad; Ali, Najma Imtaiz; Solangi, Zulfiqar; Shah, Asadullah; Ahmed, Syed Faiz (Science Publishing Corporation Inc, 2018)
Seen through the lens of the education sector social media grew a ital source of academic learning. The learning through social media occurs mainly through the collaborative approach to information sharing, where the web-based social networking sites provide the optimal platform for knowledge enhancing among colleagues, co-workers, and others. Developed economies have already recognized the significant value of learning through social media. However, developing economies such as Pakistan did not yet interpret future implications and real benefits of social aided learning. This research focuses on determining significant factors through an integrated framework that features broadly recognized technology models such as technology acceptance model (TAM) and innovation diffusion theory (IDT). The subjects of framework tested were students in higher education institutions that use social media, and the sample size was 350 students. Data analysis results, reached via SPSS software, were substantially in fever of extended model. Results reached through this study, in terms of factors with a significant influence on social media acceptance rate in Pakistani higher education institutions, are particularly crucial for students in the filed of education, located in developing countries. This should assist the increasing acceptance and use of technological solutions, benefiting both faculty and students.